PERAN KEGIATAN EKSTRAKURIKULER PALANG MERAH REMAJA (PMR) DALAM MEMBENTUK KETERAMPILAN SOSIAL(SOCIAL SKILLS)PESERTA DIDK - R. Yuni Lestari, Siti Nurasiah, Damanhuri, (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2018)
This study aims to determine (1) the implementation of PMR Extracurricular (2) The Role of PMR extracurricular aktivities in shaping the social skills of students (3) What Factors Support and in hibit PMR extracurricular aktivities in shapping skills of students in SMAN 1 Cikande. The research method Uses a qualitative descriptive approach with the subject of the study consisting of the pricipal, deputy headmaster of student affairs, coaches, speaker of PMR aktivities and PMR member of SMAN 1 Cikande. Data collections is in thefrom of interviews, observation, and documentation. As for the techinuques used to analyze data, namely the steps proposed by Miles and Huberman through data collections data reductions, data presentation, and conclusions and verification. To test and validaty of the data using source and technique triangulation. The Result of the study show that students social skills can be formed through PMR activities, namely first aid activities routina training, joint training (jungle camp), and KSR Untirta editing activities. Social skills that are formed in these activities are the development of PMR member’s emphaty by providing basic medical care for students who experience, fainting, and giddiness at school. Joint responsibility so as to create good cooperation for each member of PMR to achieve common goals, can communicate verbally and non verbally to pears and others, and has the basis of interacting tho share information, exchange ideas or experiences of fellow mwmbwers of the PMR. Supporting factors PMR extracurricular activities consist of school support, PMR member motivation in participating in PMR parents, KSR and PMI who pay attention to assist the development of PMR SMAN 1 Cikande. While the inhibiting factors is composed of inadequate infrastructure to support extracurricular activities and the absence of professional PMR trainers in the field of PMR.Keywords: Extracurricular, Youth Red Cross, Social Skill